The baltic battle of books formation and relocation of european libraries in the confessional age (c. 1500–c. 1650) and their afterlife - Nordin, Jonas 1968-; Strenga, Gustavs 1981-; Sjökvist, Peter 1974- (Library of the written word, 2023)
This book is about the creation, relocation, and reconstruction of libraries between the late Middle Ages and the Age of Confessionalization, that is, the era of religious division and struggle in Northern Europe following the Reformation and Counter-Reformation in the sixteenth and seventeenth centuries. At the time, different creeds clashed with each other, but it was also a period in which the political and intellectual geography of Europe was redrawn. Centuries-old political, economic, and cultural networks fell apart and were replaced with new ones. Books and libraries were at the centre of these cultural, political, and religious transformations, frequently seized as war booties and appropriated by their new owners in distant locations.